Midwives' experiences of performing maternal observations and escalating concerns: a focus group study - Justine Jeffery; Alistair Hewison; Laura Goodwin; Sara Kenyon (BMC, 2017)
Abstract Background For the past decade, Maternal Mortality Reports, published in the United Kingdom every three years, have consistently raised concerns about maternal observations in maternity care. The reports identify that observations are not being done, not being completed fully, are not recorded on Early Warning Score systems, and/or are not escalated appropriately. This has resulted in delays in referral, intervention and increases the risk of maternal morbidity or mortality. However there has been little exploration of the possible reasons for non-completion of maternal observations. Methods The aim of this study was to explore midwives' experiences of performing maternal observations and escalating concerns in rural and urban maternity settings in the West Midlands of England. A qualitative design involving a series of six focus groups with midwives and Supervisors of Midwives was employed to investigate the facilitators of, and barriers to the completion of maternal observations. Results Eighteen Midwives and 8 Supervisors of Midwives participated in a total of 6 focus groups. Three key themes emerged from the data: (1) Organisation of Maternal Observations (including delegation of tasks to Midwifery Support Workers, variation in their training, the care model used e.g. one to one care, and staffing issues); (2) Prioritisation of Maternal Observations (including the role of professional judgement and concerns expressed by midwives that they did not feel equipped to care for women with complex clinical needs; and (3) Negotiated Escalation (including the inappropriate response from senior staff to use of Modified Early Warning Score systems, and the emotional impact of escalation). Conclusions A number of organisational and cultural barriers exist to the completion of maternal observations and the escalation of concerns. In order to address these the following actions are recommended: standardised training for Midwifery Support Workers, review of training of midwives to ensure it addresses the increasing complexity of the maternal population, identification and agreement regarding the organisation of maternal observations among staff, an emphasis on increasing the priority placed on maternal observations in all clinical settings, and clarification and reinforcement of escalation procedures for both midwives and senior clinicians.